2021
DOI: 10.1021/acs.jpcc.1c04861
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Transport Properties of Mesoporous Doped Cerium Oxide for Energy Applications

Abstract: Hard-template nanocasted mesoporous cerium oxide possesses a unique combination of thermal stability, high surface area, and short diffusion lengths for mass and gas transport, which makes it relevant for high-temperature catalysis, sensing, and electrochemical applications. Here, we present an in-depth study of a number of mesoporous doped ceria systems, and we assess their fundamental structure and functionalities by complementary transmission electron microscopy imaging and spectroscopy, electron tomography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…Cells with a commercial CGO scaffold present similar values (1.23 ± 0.01, 1.23 ± 0.02 and 1.29 ± 0.01 eV for CGO, 5-CGO and 10-CGO cells, respectively) while a slight increase is observed employing the mesoporous scaffold (1.38 ± 0.04 eV). This difference could be caused by either the presence of small amounts of silica contamination (≈1 wt%), due to the incomplete removal of the employed mesoporous template, or dopant segregation to the interfaces, as previously reported by the authors [36,96]. Concerning ASR pol values, a clear difference in resistance scaffolds with and without infiltration is observed (due to the lack of a catalytic phase in the functional layer).…”
Section: Electrochemical Characterization Of the Infiltrated Cellsmentioning
confidence: 62%
“…Cells with a commercial CGO scaffold present similar values (1.23 ± 0.01, 1.23 ± 0.02 and 1.29 ± 0.01 eV for CGO, 5-CGO and 10-CGO cells, respectively) while a slight increase is observed employing the mesoporous scaffold (1.38 ± 0.04 eV). This difference could be caused by either the presence of small amounts of silica contamination (≈1 wt%), due to the incomplete removal of the employed mesoporous template, or dopant segregation to the interfaces, as previously reported by the authors [36,96]. Concerning ASR pol values, a clear difference in resistance scaffolds with and without infiltration is observed (due to the lack of a catalytic phase in the functional layer).…”
Section: Electrochemical Characterization Of the Infiltrated Cellsmentioning
confidence: 62%
“…In consequence, the impedance of mesoporous thin films may in principle exhibit up to three contributions, representing bulk transport, transport across the grain boundaries, and the geometric current constriction effect. However, experimental impedance data of mesoporous ceramic oxide thin films typically exhibit only one semicircle in Nyquist representation. , , …”
Section: Resultsmentioning
confidence: 99%
“…A lattice contraction χ of 70% in the z -direction is considered to account for the oblate shape of the pores. Typically, the transport properties of mesoporous thin films are measured in in-plane geometry, i.e., perpendicular to the z -direction. For the simulations, however, we consider all possible transport directions, i.e., the x -, y -, and z -direction. This means the voltage is applied between two homogeneous electrodes enclosing a single periodic unit volume, as shown exemplarily in Figure c for the z -direction.…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…The regular pore arrangement enables efficient penetration of gases or liquids into the bulk, thereby improving the accessibility of active surface sites. This characteristic structure qualifies mesoporous oxides for a variety of electrochemical applications, e.g., in the field of (photo)­electrocatalysis, as electrode materials for batteries and supercapacitors or gas sensors. Several studies have shown that mesoporous architectures are favorable for electrochemical applications, which is mostly attributed to their large specific surface area.…”
mentioning
confidence: 99%